Alterações do perfil médio facial no tratamento da má oclusão de classe II, divisão 1 de Angle com aparelho extrabucal de Kloehn - Abdala, Anamaria Miranda [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
A presente pesquisa foi de natureza retrospectiva e desenvolvida com o intuito de avaliar as alterações ocorridas no perfil médio facial em pacientes classe II divisão 1 de Angle, tratados com o aparelho extrabucal de Kloehn. A amostra foi selecionada e constituída de 30 indivíduos, sendo que, 18 indivíduos para o grupo experimental tratados com aparelho extrabucal de Kloehn e 12 indivíduos para o grupo controle que não receberam nenhum tipo de tratamento no período analisado. Foram realizadas telerradiografias cefalométricas no inicio (T1) e no final (T2) do tratamento para todos os indivíduos. As análises dos dados, permitiram concluir que o tratamento com aparelho extrabucal de Kloehn para pacientes em classe II divisão 1, de Angle não apresentou alterações estatisticamente significantes em relação ao perfil mole facial, ângulo nasolabial, espessura e comprimento do lábio superior, comparado ao grupo não tratado. Por outro lado, houve uma resposta estatisticamente significante (p<0,05) quanto a restrição do deslocamento anterior da maxila com resultados esqueléticos e dento-alveolares para a correção desta má oclusão.

This research was of nature retrospect and developed with intention to evaluated changes occurred in the facial media profile in patients class II division 1 of Angle, treated with the Kloehn headgear appliance. The sample was selected and consisted of 30 individuals, 18 of the experimental group, treated with Kloehn headgear appliance and 12 of the control group that had not received any type of treatment in the analyzed period. Cephalometric radiographs for all patients were taken at the pretreatment (T1) and posttreatment (T2). The average age pretreatment of experimental group was 9,3 years, and for the group control the average age pretreatment was 10,6 years. The results had been described through traditional cephalometrics measures and for movement of related cephalometrics points to the soft profile in relation to coordinates X and Y, gotten 70 for low in relation to the sela nasio line (S-N). The results of treatment and the changes provoked for the normal growth, had been analysed and compared by means t student test , the levene test was applied for the analysis of the variances. Evaluation of reprodutibility (error of the method) with index of agreement above of 98% was realized. The analyses of results had allowed conclude that the treatment with Kloehn headgear appliance for patients Angle class II, division1 did not showed significant statistical changes in relation to the facial soft profile, nasolabial angle, thickness and length of the superior lip, when compared with untreatment group. On the other hand, it had results statistical significant (p<0,05) to the restriction of the anterior displacement of the jaw with skeletals and dentoalveolars results for the correction of this maloccclusion.
Keywords: Aparelhos de tração extrabucal; Má oclusão de Angle Classe II; Odontologia - Aspectos estéticos; Maloclusão de classe II; Heardgear appliances; Angle class II malocclusion; Aesthetic dental